2012
DOI: 10.1172/jci63930
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-derived endotrophin promotes malignant tumor progression

Abstract: Adipocytes represent a major cell type in the mammary tumor microenvironment and are important for tumor growth. Collagen VI (COL6) is highly expressed in adipose tissue, upregulated in the obese state, and enriched in breast cancer lesions and is a stimulator of mammary tumor growth. Here, we have described a cleavage product of the COL6α3 chain, endotrophin (ETP), which serves as the major mediator of the COL6-mediated tumor effects. ETP augmented fibrosis, angiogenesis, and inflammation through recruitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
342
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(350 citation statements)
references
References 52 publications
5
342
1
2
Order By: Relevance
“…Moreover, the ECM can serve as an endocrine organ due to the signalling potential of certain fragments released by proteolysis, creating ligands with paracrine and potential endocrine functions [3]. Endotrophin (Pro-C6) is a soluble fragment of the C-terminal α3 chain of type VI procollagen that is released by naturally occurring proteolysis [4,8,22,26]. Here we demonstrate that serum endotrophin levels are predictive of a response to the insulin sensitisers, pioglitazone and balaglitazone, in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the ECM can serve as an endocrine organ due to the signalling potential of certain fragments released by proteolysis, creating ligands with paracrine and potential endocrine functions [3]. Endotrophin (Pro-C6) is a soluble fragment of the C-terminal α3 chain of type VI procollagen that is released by naturally occurring proteolysis [4,8,22,26]. Here we demonstrate that serum endotrophin levels are predictive of a response to the insulin sensitisers, pioglitazone and balaglitazone, in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, endotrophin levels have been shown to reflect insulin sensitivity, food intake and energy balance, as well as angiogenesis [4,5,8]. Accordingly, suppression of endotrophin improves insulin sensitivity and attenuated adipose tissue inflammation in animals [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marrows of these patients contain large numbers of adipocytes. Adipocytes are known to be involved in tumor progression and metastasis, 32,33 which may be partly owing to their negative effects on hematopoiesis; 13 however, little is known regarding the specific roles that these cells have in the metastatic process. A recent study demonstrated that marrow adipocytes support bone metastasis of prostate cancer, 34 as more PC3 cells, a prostate cancer cell line, grew in the bone marrow of animals receiving a high-fat diet than in that of animals on a regular diet.…”
Section: Adipocytesmentioning
confidence: 99%
“…Une de ces protéines, qui est très exprimée par les adipocytes péritumoraux et qui favorise la croissance des tumeurs mammaires in vivo, est le collagène VI (Col6) [26]. Il a été récemment montré qu'un des fragments de clivage du collagène, l'endotrophine, agissait comme une molécule de signalisation et augmentait la fibrose, l'angiogenèse et l'inflammation dans le microenvironnement des tumeurs mammaires, favorisant ainsi l'agressivité tumorale et, en particulier, les métastases [27]. Les CAA expriment aussi la MMP11 (ou stromélysine 3), dont l'expression favorise la croissance des tumeurs mammaires [22].…”
Section: Le Tissu Adipeux Ou Plutôt Les Tissus Adipeux : De L'importaunclassified